(3cJGH eYQaI CfhGY Ydhe GdMOjKs - (3YKeGf Hf YHO GdQMef (B((3UdGM GdOjf(B) (3GHf YKeGf Hf ehSi Hf CHj GdfUQ GdfUQj GdTgQRhQj GdcQOj GdTQNGfj, CHh YeQh, Jbj GdOjf, GdeYQha HGHf GdUdGM,J (B643 (3g` s
(3ChdgG (B:s
(3jHOC HGdfhY GdChd ef CfhGY Ydhe GdMOjK eYQaI GdUMjM ef GdMOjK s
(3BNQgG (B:s
(3jfJgi HGdfhY GdKGdK hGdSJhf eYQaI ef NdW s
(3obQjA Ydi GdeDda hYdjg NWgs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B207 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B257s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1161s
Keywords: (3GdMOjK h GdeUWdMs